Type I interferons induced upon respiratory viral infection impair lung metastatic initiation - Ana Farias; Victoria L. Bridgeman; Felipe S. Rodrigues; Franz Puttur; Amber Owen; Stefanie Ruhland; Rute M. M. Ferreira; Matthias Mack; Ilaria Malanchi; Cecilia Johansson (Proceedings of the National Academy of Sciences, 2026)
Metastatic breast cancer accounts for 7% of cancer-related deaths, with the lungs being a common site of cancer spread. In parallel, lower respiratory tract infections, including those caused by respiratory syncytial virus (RSV), remain a common cause of morbidity and mortality worldwide. Acute viral respiratory infections induce marked changes in the lung. However, how these changes influence metastasis initiation and cancer progression remains unclear. Using breast cancer and other cancer cell types in an experimental lung metastasis model, we show that RSV infection impairs tumor cell seeding and early growth in the lung, resulting in fewer metastatic nodules. We demonstrate that restriction of metastatic spread is due to alterations in the lung environment mediated by RSV-induced type I interferons (IFNs). Consistent with this idea, intranasal administration of recombinant IFN-α is sufficient to recapitulate the anti-metastatic effect of RSV infection. Using single cell RNA sequencing supported by in vivo and ex vivo validation, we show that IFN-α influences interactions between epithelial/endothelial cells and cancer cells. Furthermore, both RSV infection and IFN-α administration trigger marked local and systemic upregulation of Galectin-9, an IFN-inducible protein associated with acute respiratory infection in humans. Treatment of cancer cells with Galectin-9 alone is sufficient to restrict metastatic seeding. Altogether, our results suggest that type I IFNs induced by respiratory virus infection render the lungs less permissive to cancer cell seeding and consequently interfere with the ability of tumor cells to successfully initiate metastatic colonization.